Two new land planarian species (Platyhelminthes: Tricladida) from the Cerrado biome in southwestern Brazil - Marques, Alessandro Damasceno; Hartmann, Alef; Valiati, Victor Hugo; Leal-Zanchet, Ana Maria (Zootaxa, 2022)
Most Neotropical land flatworm species are known from areas of the Atlantic Forest. Herein, we describe two new land planarian species from areas of semideciduous forest in the Cerrado biome in southwestern Brazil. Paraba aurantia Marques & Leal-Zanchet, sp. nov. can be distinguished from its congeners by the wide black median band on the dorsum, eyes occupying almost the entire dorsal surface, prostatic vesicle twisted and asymmetrical with proximal portions forked, and female atrium with an ample lumen lined by a low epithelium with stratified appearance. Pasipha liviae Marques & Leal-Zanchet, sp. nov. shows a narrow longitudinal dorsal stripe, collar-shaped pharynx, and prostatic vesicle with a pear-shaped proximal portion and a globose distal portion separated by a constriction. In addition, P. liviae can be distinguished from its congeners by molecular analyses from the cytochrome c oxidase subunit I gene (COI). Phylogenetic analyses suggest that P. liviae is closely related to P. hauseri, which occurs in areas of semidseciduous forest in southern Brazil.